Characterization of strike-slip fault zones by gradient-driven signed pressure force model in the Northeast Sichuan Basin - Li, Siyao; Huang, Xuri; Tang, Shuhang; Wu, Guanghui; Feng, Liang; Li, Mengcheng (Frontiers in Earth Science, 2025)
The Sichuan Basin is China’s largest natural gas-producing basin and presents significant challenges for deep oil and gas exploration due to its complex geological conditions. Recent studies in the Northeast Sichuan Basin, particularly the Kaijiang-Liangping (KJ-LP) Trough, have identified the presence of strike-slip faults which may influence the deposition of reefs and shoals. Understanding the controlling influence of these fault zones on the distribution and development of hydrocarbon reservoirs is crucial for effective exploration. Traditional fault identification methods are less effective due to the weak seismic response in this area, which results from the complex geological conditions and lack of dissolution cavities. Predicting fault-related fractures remains a key challenge. To address these challenges, this paper proposes a novel fault characterization approach using the Gradient-Driven Signed Pressure Force (G-SPF) Active Contour Model (ACM), an image-processing-based boundary identification technique. The method begins by selecting tensor and symmetry as the primary optimization attributes. Gradient information is then integrated into the ACM to improve the vertical continuity of fault identification. Finally, a two-step iterative process is employed to separately characterize the fault core and damage zone, improving fault zone delineation. The improved methodology significantly enhances strike-slip fault zone characterization. The results also reveal that strike-slip fault zones serve as vertical migration pathways for deep-source hydrocarbons and they facilitate the lateral migration from source rocks within the trough. By integrating structural analysis with sedimentary characteristics, this study highlights the critical role of strike-slip fault zones in hydrocarbon migration and accumulation.